2018
DOI: 10.1111/jfs.12601
|View full text |Cite
|
Sign up to set email alerts
|

Virulence genes and antibiotic resistance of Salmonella recovered from a wet market in Thailand

Abstract: Salmonella is an important foodborne pathogen, which is often found on chicken meat and various sites in wet markets in Southeast Asia, thus requiring close monitoring for effective control measures. In this study, 130 samples from chicken meat, environment, and wastewater from three chicken meat stalls at a wet market were tested for Salmonella spp. For stall A, B, and C, 20 (44.4%), 8 (17.4%), and 9 (23.1%) samples were positive for Salmonella, respectively. In this study, Salmonella was often detected on wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Poultry meat and its products have served as major sources of Salmonella spp., which have caused human and animal diseases as well as economic losses to the poultry industry (Barbour et al, 2015). In Thailand, Salmonella contamination in broilers and poultry meat has been previously reported (Sripaurya et al, 2019). Although Salmonella contamination in broiler farms (at the beginning of the poultry production chain) is commonly reported, Dookeran et al (2012) observed that broiler carcass contamination with Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Poultry meat and its products have served as major sources of Salmonella spp., which have caused human and animal diseases as well as economic losses to the poultry industry (Barbour et al, 2015). In Thailand, Salmonella contamination in broilers and poultry meat has been previously reported (Sripaurya et al, 2019). Although Salmonella contamination in broiler farms (at the beginning of the poultry production chain) is commonly reported, Dookeran et al (2012) observed that broiler carcass contamination with Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…The whole chicken carcass, vendor, and consumer may be infected with Salmonella due to poor sanitary and hygienic practices. Even there is a great scope to spread and transmission of Salmonella enterica serovars in the agricultural food chain in the wet markets as most products are sold at ambient temperature and exposed to the environment (Sripaurya et al, 2019). A preceding study stated the incidence of Salmonella in various sites of the wet markets indicated a cause of cross-contamination in meat during selling through food contact surfaces or equipment (Nidaullah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, coliforms are considered appropriate safety indicators for RTE meat products. Salmonella strains colonize chickens with a probability of 17 to 44% (Sripaurya, Ngasaman, Benjakul, & Vongkamjan, 2019). Although this foodborne pathogen is usually killed by heating, it can survive if the heating conditions are inadequate (JFHA, 2015).…”
Section: Discussionmentioning
confidence: 99%